Evaluation of four sorghum hybrids in a gluten-free noodle system - Liu, Liman (Kansas State University, 2009)
The number of people diagnosed with celiac disease has increased and subsequently the market for gluten-free products is rising. Sorghum has been identified to be a safe grain to use as a wheat alternative for the celiac community. There are many sorghum hybrids that are commercial available for use in food and feed. Noodles are selected for the growing market in the US and the lack of research and availability for sorghum noodles. Viscoelastic properties are crucial for making acceptable noodles which makes this research more challengeable. The research hypothesis is that sorghum can be used in making gluten-free noodles and there are end product quality differences that exist among the hybrids in production of gluten-free noodles. A series of chemical and physical analyses were conducted to compare four sorghum hybrids (Orbit, NE #8, F-525, NE #4) in a gluten-free noodle system. The noodles were formulated with 100% sorghum flour and the other functional ingredients including dried whole eggs, egg whites, xanthan gum and corn starch. Sorghum noodles were significantly different in color, texture and cooking quality among hybrids. The starch properties were found to have more effect than protein content on sorghum noodle qualities. Sorghum flour with fine particle size and low ash content was crucial for making acceptable sorghum noodles. Noodles made from sorghum F-525 exhibited some properties significantly closer to the commercial wheat flour noodles.
Keywords: Sorghum; gluten-free; noodle; Agriculture, Food Science and Technology (0359)